STUDI TENTANG PENGARUH LINGKUNGAN KELUARGA TERHADAP TOLERANSI BERAGAMA DI PERUMAHAN BTN TPI (TAMAN PERAWANG INDAH) KECAMATAN TUALANG, KABUPATEN SIAK - Dela, Nurma; Eddison, Ahmad; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : The influence of the family environment on Religious Tolerance that occurs in BTN TPI Housing (Taman Perawang Indah) becomes very important for the creation of a good tolerance environment, especially in religious tolerance by children. Therefore, parents are important in instilling the values of tolerance to their children such as mutual respect between religious people, teaching symbols of other religions, and motivating children to associate with friends who are different beliefs with them. The formulation of this research problem is how the influence of the family environment on religious tolerance in btn TPI housing Tualang Subdistrict, Siak Regency. The purpose of this study was to find out how the influence of the family environment on religious tolerance in btn TPI housing Tualang Subdistrict, Siak Regency. The practical benefit of this study is to find out how the influence of the family environment on religious tolerance in btn TPI housing Tualang Subdistrict, Siak Regency, and can be used as a reference material in carrying out further research relevant to this research. This research method is a quantitative descriptive, data collection instrument using a questionnaire consisting of 28 statements. The population in this study was school-age children in btn TPI housing (Taman Perawang Indah) consisting of 167 children, with a sample withdrawal of 20% of the population to 33 respondents using the Proposionate Stratified Random Sampling Technique. Based on the results of the calculation of SPSS version 23 obtained the value of Fhitung > Ftabel which is 5,532 > 4,160, then Ho was rejected and Ha was accepted which means variable X (Family Environment) affects variable Y (Religious Tolerance). The coefficient of determination (R Square) of 0.389 which means that family relationships affect religious tolerance is 15.1%, meaning that there is a